Motivation for career choice and job satisfaction of GP trainees and newly qualified GPs across Europe: a seven countries cross-sectional survey - Roos, Marco; Watson, Jessica; Wensing, Michel; Peters-Klimm, Frank (Education for primary care, 2014)
What is already known in this areaRecruitment and retention of general practitioners is a major concern in many European countries.Previous studies looking at motivation revealed a perception that general practice had an inferior clinical content but superior lifestyle than hospital medicine, with the choice of general practice as a career often based on negative judgements.What this work addsCurrent trainees and newly qualified GPs across seven European countries choose general practice for positive reasons such as ‘compatibility with family life’ and ‘the challenging medically broad discipline’.Overall levels of career satisfaction are high.suggestions for future researchDifferences between countries in motivation and satisfaction should be explored further with qualitative studies.
Published online: 07 Oct 2015
Gesehen am 12.02.2021